Enterprise knowledge capital - Laperche, Blandine (ISTE Ltd ; John Wiley & Sons, Inc., 2017)
"Thoroughly grounded in an extensive body of international research and analysis, this book investigates the concepts surrounding a firm's knowledge capital. These concepts play an integral part in the evolution of economic and managerial thinking, particularly in relation to the themes of firm, knowledge and innovation. The author advocates a greater socialization of the production of knowledge capital that stands in contradiction to the strong appropriation strategies that are predominant today. This book presents a historical analysis of the facts with a strong basis in the recent literature in economics and innovation management as well as in case studies of CAC 40 companies that have been conducted over the course of the past few years."- Resumé vydavatel
Keywords: znalostní management; management inovací; knowledge management; innovation management; monografie; elektronické knihy; monographs; electronic books